Language Style Used By The Main Characters In Green Book Movie - Ni Made Sanimawati; Ni Ketut Sri Rahayuni; I Made Netra (Stilistika : Journal of Indonesian Language and Literature, 2022)
The aims of this study is to find out the types of language style and find out the dominant types of language style used by the main characters in Green Book Movie. The data were taken from the movie entitled Green Book. The data were collected by documentation and note-taking techniques. This study used mixed method for analyzing the data. The data were analyzed using theory of language style proposed by Martin Joos (1967) and the theory of factors influence the used of language style by Holmes (1992) as support theory. In presenting the data, this study applied both formal and informal techniques and methods. The result of the study shows that is found twenty data of language style that used by the main characters and all types of language style were can found in the movie used by the main characters. While each of the characters not used one out of five types of language style. The dominant type of language style is casual style which was used by an actor named Tony Lip. Meanwhile, the factor that influences the use of language style are setting, participant and function.